Use of an axial magnetic field to suppress convection in the solvent of Ge0.98Si0.02 grown by the travelling solvent method. (1st December 2004) - Abidi, L.; Saghir, M.Z.; Labrie, D.
A three dimensional numerical simulation of the effect of an axial magnetic field on the fluid flow, heat and mass transfer within the solvent of Ge0.98 Si0.02 grown by the travelling solvent method is presented. The feed rod consists of a Ge0.85 Si0.15 polycrystalline material, a Ge0.98 Si0.02 rod which acts as the solvent and a germanium seed located at the bottom of the sample. It is found that a strong convective flow exists in the solvent, which is known to be undesirable to achieve a uniform crystal. An external axial magnetic field is applied to suppress this convection. By increasing the magnetic induction it is observed that the intensity of the flow at the centre of the crucible reduces at a faster rate than near the wall. This phenomenon creates a stable and flat growth interface and the silicon distribution in the horizontal plane becomes relatively homocentric. The maximum velocity is found to obey a logarithmic law with respect to the Hartmann number Umax ∝ Ha -7/4 .